Research Constraints in the Pandemic Era: a Mixed- Method Projective Analysis - Sellam, Latifa (LANGUAGE ART, 2024)
The current study addresses the research approaches adopted by master’s students in conducting final projects in the time of the pandemic end-phase. With a mixed-method, we project the research trail as well as the outcomes. The results postulate that there is an aggregation of factors resulting blatant mediocrity in research, which is attributed first, to the lack of constant supportive supervisory accompaniment. Second, mental health issues that appeared to be detrimental. Third, the unsupportive atmosphere with respect to reaching target populations and peer-exchange. Fourth, resorting to misconduct, and that, dissatisfaction feeling among the participants was predominantly noticeable, and that, they could do better in normal circumstances.